The role of leadership identity in business and public sectors: a content analysis approach - Engin, Sevinc; Kasap, Fevzi (Frontiers in Psychology, 2025)
BackgroundLeadership is a multifaceted concept shaped by professional, cultural, and organizational contexts. This study examines how business leaders conceptualize leadership and its influence on the construction of leadership identities. By focusing on sector-specific perspectives, the research highlights the varying definitions and roles of leadership across different professional environments.MethodA qualitative approach was employed to analyze leadership narratives from 71 participants, including CEOs, entrepreneurs, media professionals, politicians, and bureaucrats. Data were collected through in-depth interviews, and content analysis was used to identify themes and patterns in how leaders perceive and define their roles.ResultsThe findings reveal sectoral variations in leadership conceptualizations. Business leaders and entrepreneurs emphasize innovation, success, and strategic thinking. Journalists and media professionals prioritize influence and communication, while bureaucrats and politicians focus on ethics, public service, and societal values. These distinct perspectives demonstrate how leadership identities are shaped by the normative pressures and expectations of different professional contexts.ConclusionThe study underscores the contextual nature of leadership perceptions and their role in shaping leadership identity. It provides valuable insights into how leadership is constructed and understood across sectors, contributing to leadership theory and practice. Future research should expand the scope to include a wider range of professional groups and conduct comparative analyses to deepen understanding of the factors influencing leadership development.